Validity of the Brazilian version of WHOQOL-BREF in depressed patients using Rasch modelling Validez de la versión brasilera de WHOQOL-BREF en pacientes deprimidos usando el modelo del Rasch Validade da versão brasileira do WHOQOL-BREF em pacientes deprimidos usando o modelo de Rasch - Neusa Sica da Rocha; Marcelo Pio de Almeida Fleck (Universidade de São Paulo, 2009)
OBJECTIVE: To assess the validity of the Brazilian version of the World Health Organization Quality of Life Instrument - Abbreviated version (WHOQOL-BREF) in adults with major depression, using Rasch modelling. METHODS: Study analyzing data from the baseline sample of the Longitudinal Investigation of Depression Outcomes in Brazil, including a total of 208 patients with major depression recruited in a primary care service in Porto Alegre (Southern Brazil), in 1999. The Center for Epidemiological Studies Depression Scale was used to assess intensity of depression; the WHOQOL-BREF to assess generic quality of life; and the Composite International Diagnostic Interview version 2.1 for the diagnosis of depression. RESULTS: In the Rasch analysis, the four domains of WHOQOL-BREF showed appropriate fit to this model. Some items needed adjustments: four items were rescored (pain, finances, services, and transport); two items (work and activity) were identified as having dependency of responses, and one item was deleted (sleep) due to multidimensionality. CONCLUSIONS: The validation of the WHOQOL-BREF Brazilian version using Rasch analysis complements previous validation studies, evidencing the robustness of this instrument as a generic cross-cultural quality of life measure. OBJETIVO: Evaluar la validez de la version brasilera del Instrumento de Calidad de Vida de la Organización Mundial de la Salud, abreviado en inglés WHOQOL-BREF, en adultos con depression, usando el modelo de Rasch. MÉTODOS: Se analizaron datos de la base de Investigación Longitudinal de Resultados de Depresión en Brasil, incluyendo un total de 208 pacientes con derpesión mayor recluidos en servicio de ciudado primario en Porto Alegre (Sur de Brasil), en 1999. El Centro de Estudios Epidemiológicos de Depresión fue usado para evaluar la intensidad de la depresión; el WHOQOLBREF para evaluar la calidad genérica de vida; y la Entrevista Internacional Compuesta para el Diagnostico versión 2.1 para el diagnostico de la depresión. RESULTADOS: En el análisis Rasch, los cuatro dominios del WHOQOL-BREF mostraron ajuste apropiado con el modelo. Algunos ítems necesitaron ajustes: cuatro ítems fueron revalorados (dolor, financias, servicios y transporte), dos ítems (trabajo y actividad) fueron presentaron dependencia de respuestas, y uno de los ítems fue eliminado (dormir) debido a multidimensionalidad. CONCLUSIONES: La validación del WHOQOL-BREF versión brasilera usando análisis Rasch complementa estudios de validación previa, evidenciando lo robusto de este instrumento como una medida genérica transcultural de la calidad de vida. OBJETIVO: Testar a validade da versão brasileira do World Health Organization Quality of Life Instrument, abbreviated version (WHOQOL-BREF) em adultos com depressão maior, usando o modelo de Rasch. MÉTODOS: Estudo utilizando dados secundários da amostra brasileira basal do "Longitudinal Investigation of Depression Outcomes", constituída por 208 pacientes com depressão maior, recrutados em um serviço de atenção primária de Porto Alegre, RS, em 1999. Os instrumentos utilizados foram: a Center for Epidemiological Studies Depression Scale para avaliar a intensidade da depressão; a versão brasileira do WHOQOL-BREF, como medida de qualidade de vida genérica; e a Composite International Diagnostic Interview, version 2.1 para o diagnóstico de depressão. RESULTADOS: Após usar a análise de Rasch, os quatro domínios do WHOQOL-BREF se mostraram adequados ao modelo de Rasch. Alguns itens necessitaram de ajustes: quatro itens foram recodificados (dor; finanças, serviços e transporte), 2 itens (trabalho e atividade) mostraram dependência de respostas, e 1 item foi retirado (sono), por apresentar sinal de multidimensionalidade. CONCLUSÕES: A validação da versão brasileira do WHOQOL-BREF usando a análise de Rasch complementa os estudos prévios de validação, confirmando a importância deste instrumento como uma medida transcultural genérica de qualidade de vida.